Analysis of 65 pregnancies in 34 women with five different forms of inherited platelet function disorders. (21st April 2015) - Civaschi, Elisa; Klersy, Catherine; Melazzini, Federica; Pujol‐Moix, Nuria; Santoro, Cristina; Cattaneo, Marco; Lavenu‐Bombled, Cécile; Bury, Loredana; Minuz, Pietro; Nurden, Paquita; Cid, Ana R.; Cuker, Adam; et al.
Summary This study evaluated 65 pregnancies in 34 women with five different inherited platelet function disorders. Gestation was similar to that of the general population. Severe bleeds requiring blood transfusions were observed in 50% of deliveries in Glanzmann thrombasthenia (GT), but not in the patients with delta storage pool disease, Hermansky‐Pudlak syndrome, P2Y12 defect or defect of thromboxane A2 receptor. Of note, severe haemorrhage also occurred in women with GT who had received prophylactic platelet transfusions, suggesting that better preventive treatments are required. Diagnosis and degree of spontaneous bleeding tendency before pregnancy were reliable parameters to predict the delivery‐related bleeding risk.